Epigenetic mechanisms regulating differentiation of neural stem/precursor cells. (December 2014) - Adefuin, Aliya Mari D; Kimura, Ayaka; Noguchi, Hirofumi; Nakashima, Kinichi; Namihira, Masakazu
Differentiation of neural stem/precursor cells (NS/PCs) into neurons, astrocytes and oligodendrocytes during mammalian brain development is a carefully controlled and timed event. Increasing evidences suggest that epigenetic regulation is necessary to drive this. Here, we provide an overview of the epigenetic mechanisms involved in the developing mammalian embryonic forebrain. Histone methylation is a key factor but other epigenetic factors such as DNA methylation and noncoding RNAs also partake during fate determination. As numerous epigenetic modifications have been identified, future studies on timing and regional specificity of these modifications will further deepen our understanding of how intrinsic and extrinsic mechanisms participate together to precisely control brain development.